Peran Pembiayaan Murabahah di BMT Mandiri Sejahtera Cabang Sugio dalam Meningkatkan Pendapatan UMKM Pasar Sugio Lamongan - Nurul Syafaah; Khozainul Ulum (Universitas Islam Lamongan, 2022)
Small and medium micro enterprises (MSMEs) has the important role in the community for expanding employment and giving economic services that spread to the community, increasing business income and achieving benefit and prosperity among others. MSMEs basically need the support of micro finance institutions which provides the funding to raise the financial asset of MSME using sharia system. This study aims at answering the question about the role of mura>bahah financing in BMT Mandiri Sejahtera Branch Sugio Lamongan for increasing the income of small and medium micro enterprises (MSME) of Sugio Market. This is qualitative research which is also called naturalistic research method because the research have the interview, observation, and documentation. This study uses qualitative descriptive analysis technique to analyze data which tells about mura>bahah financing held by BMT Mandiri Sejahtera Branch Sugio Lamongan. The findings reveal that mura>bahah financing in BMT Mandiri Sejahtera Branch Sugio Lamongan plays an important role in improving small and medium micro enterprises of Sugio Market.